The cardiac troponin response during high-intensity interval training - Burtscher, M.; Niebauer, J. (Scandinavian Journal of Medicine & Science in Sports, 2019)
Cardiac troponins (cTn) like the high-sensitivity troponin T (hs-cTnT) have become indispensable diagnostic markers of cardiomyocyte damage in several cardiac diseases but above all in patients with coronary artery disease with or without myocardial infarction. However, cTn were also shown to increase especially after prolonged strenuous exercise like (ultra)marathon running